Utilitarianism: Doctrinal analysis evolution of thought - Górecki, Olgierd (Annales. Etyka w Życiu Gospodarczym, 2019)
Utilitarianism as an innovative and original stream of ethical and political thought has enriched the philosophical discourse of the last three centuries. Utilitarian thinkers claim that maximization of pleasure correlated with minimization of pain is the correct way to create an objective catalog of rules or behaviors that result in the formation of the highest utility for a society and its individuals. From a methodological perspective, there are differences among the utilitarian philosophers on issues such as: happiness, pleasure or utility guide to diametrical disaccord on an ethical or institutional area. The present analysis of the utilitarian thought represents some of the interesting differences in interpretation of this doctrine. However, utilitarianism does not include logical or intellectually strong arguments for the protection of an individual’s rights against the interest of people at large. Thus, this doctrine during the 18th and the 19th centuries postulated the political egalitarianism. Nowadays, utilitarianism has lost its strong ethical position. In the past, utilitarianism was a political instrument to protect most of the people in a society from an arbitrary reigning of small elite groups. In recent times, this thought legitimizes the coercion of the majority will regardless of the fact that other smaller groups may have different political views. Such thinking allows to objectify the individual man which is only identified with instrumentality to maximization of utility. The author analyzes the writings of Jeremy Bentham, John Stuart Mill and Herbert Spencer, and compares their doctrines with the scientific literature and forwards a basic thesis on the universal principles of utilitarianism. The author argues that the actual rules of political ethics under conditions of limitation theory of utility append the law of inviolability of the natural rights of an individual.